Challenging power and unearned privilege in physiotherapy: lessons from Africa - Lurch, Stephanie; Cobbing, Saul; Chetty, Verusia; Maddocks, Stacy (Frontiers in Rehabilitation Sciences, 2023)
Power and unearned privilege in the profession of physiotherapy (PT) reside in the white, Western, English-speaking world. Globally, rehabilitation curricula and practices are derived primarily from European epistemologies. African philosophies, thinkers, writers and ways of healing are not practiced widely in healthcare throughout the globe. In this invited perspectives paper, we discuss the philosophies of Ubuntu and Seriti, and describe how these ways of thinking, knowing, and being challenge Western biomedical approaches to healthcare. We believe implementing these philosophies in the West will assist patients in attaining the health outcomes they seek. Further we call for Western professionals and researchers to stand in solidarity with their African counterparts in order to move towards a diversity of practitioners and practices that help to ensure better outcomes for all.